Innovation, créativité et qualité de vie au travail : proposition et expérimentation d’un dispositif d’innovation transitionnelle - Nadège Guidou; Philippe Sarnin (Activités, 2021)
While according to their political name so-called quality of working life (QWL) approaches are described as seeking an alliance between economic performance and social performance, they still give rise to a number of reservations. Indeed, if QWL is not to be just another “lexical shift” in the field of mental health at work (Clot, 2019), it is necessary to seriously consider the question of the methodologies to be developed in order for it to respond “to the socio-organisational problems that arise in the life of the company […] and not to be an overhang constituting yet another project to be added […]” (our translation, Levet, 2013, p. 104). In this perspective, the objective of this article is to present a methodology based on organisational innovations generated from transitional activities that are sources of creativity and health (West & Far, 1990; Winnicott, 1999/1948; Lhuilier & Roche, 2009). This approach, known as transitional innovation, specifically aims at overcoming the difficulty of moving from diagnosis to sustainable transformation and at accompanying the actors through the trials and tribulations of the process. It was tested for the first time in an occupational health department that was to intervene in a higher education institute that was experiencing major psychosocial problems. The analysis of its results made it possible to observe transformations in the organisation and work situations and their sustainability one year after the end of the scheme.